Ariel's stencil book (Bath : Parragon, 2011)
"Learn to draw Ariel and her friends with this enchanting stencil book. You can make pretty jewellery and gifts too, with the lovely pop-out shapes!"--Cover.
On board pages.
Keywords: Children's stories; Stencil work -- Juvenile literature